Ambulance nurses' experiences of patient relationships in urgent and emergency situations: A qualitative exploration. (June 2019) - Svensson, Cecilia; Bremer, Anders; Holmberg, Mats
Background: The ambulance service provides emergency care to meet the patient's medical and nursing needs. Based on professional nursing values, this should be done within a caring relationship with a holistic approach as the opposite would risk suffering related to disengagement from the patient's emotional and existential needs. However, knowledge is sparse on how ambulance personnel can meet caring needs and avoid suffering, particularly in conjunction with urgent and emergency situations. Aim: The aim of the study was to explore ambulance nurses' experiences of relationships with patients in urgent and emergency situations. Methods: Data collection was performed using individual open-ended interviews with six ambulance nurses. The data were analyzed using a thematic analysis. Results: Relationships with patients during urgent and emergency assignments emerged as three themes: " Ambiguous silence, " " Professional competence " and " Challenging inadequacy " comprising eight sub-themes in total. The result shows that the ambulance nurses found it difficult to prioritize between medical care and establishing a caring relationship with the patient. However, sometimes a wordless relationship was perceived sufficient and considered a first step towards a verbal relationship. Conclusions: Ambulance nurses experience that a caring relationship cannot and does not need to be prioritized in the acute stage. This uncovers a dichotomy approach to medical care versus caring relationships that exclude a holistic approach. Thus, patients' emotional, existential and physical needs are not considered as equally important. Clinical relevance: It is important to stimulate reflection on core ethical nursing values, in training and simulation exercises among clinically active ambulance nurses.